BIOLOGICAL AND MORPHOLOGICAL CHANGES IN THE SKIN AFTER LASER REMOVAL OF TATTOOS AND PERMANENT MARKS - Mikalai Varabyou (Web of Journals Publishing, 2025)
This article summarizes current data on biological and morphological changes in the skin after laser tattoo and permanent makeup removal. It examines the mechanisms of pigment destruction (photothermal and photoacoustic effects), the primary inflammatory response, dermal remodeling, and structural changes in the epidermis. Key cellular and molecular processes, including the activation of macrophages, cytokines, and matrix metalloproteinases, are analyzed.
Keywords: Laser tattoo removal, permanent makeup, biological changes, skin morphology, photothermolysis, photoacoustic effect, dermal remodeling, inflammatory response, macrophages, matrix metalloproteinases.